(untitled) (Comprehensive Journal of Science, 2026)
This study investigates the phenomenon of the absence or non-utilization of the Teacher’s Book in primary English language teaching, with particular reference to Libyan schools. It aims to identify the underlying causes of this absence and to examine its pedagogical implications for teachers’ instructional practices and students’ learning outcomes. Adopting a quantitative research design, the study collected data through a structured online questionnaire administered to thirty primary school English language teachers in Al-Abyar. The findings reveal that the Teacher’s Book plays a pivotal role in supporting lesson planning, ensuring curriculum coherence, enhancing classroom performance, and improving students’ learning outcomes. The absence of this resource leads to inconsistencies in teaching quality, reduced teacher confidence, and weakened alignment between curriculum objectives and classroom practices. The study concludes that the Teacher’s Book is not merely a supplementary resource but a fundamental pedagogical tool, particularly at the primary level. Accordingly, the study recommends the mandatory provision of the Teacher’s Book, alongside targeted professional development programs to promote its effective and flexible use.